The Needs of Street Furniture in the Pedestrian on Urip Sumoharjo Yogyakarta Street - Berlian Putrayasa, Ilham; Hidayah, Retna; Dahar Minghat, Asnul (International Journal of Engineering and Technology, 2018)
The background of the pedestrian in Urip Sumoharjo Yogyakarta street which conditions are not comfortable for pedestrians to pass, so as to improve the comfort of the pedestrian, in this study try to understand street furniture needed for pedestrian comfort in pedestrians on Urip Sumoharjo Yogyakarta street. Data was collected using a survey method with a questionnaire containing closed questions. The data analysis technique used in this research is quantitative descriptive data analysis. Based on the results of the study showed that men prefer to walk than women, the time when people decide to walk most choose when they go to exercise, the distance traveled by people when deciding to walk is 300-600 meters, street furniture is very much needed for pedestrian comfort in the pedestrian on Urip Sumoharjo Yogyakarta street are street lights, bins, seating, and public toilets. While pedestrians are needed enough are traffic signs, shelters, bollards, and road guardrail. Pedestrians need less is flower pots, fountains and warnings, and waste containers.Â Â